A Study on the Relationship between Advertising and Marketing Communication - , Saju K James, Dr Abhiram Kulshreshtha (International Journal of Scientific Research and Management (IJSRM), 2017)
Advertising or advertizing in business is a form of marketing communication used to encourage, persuade, ormanipulate an audience (viewers, readers or listeners; sometimes a specific group) to take or continue to takesome action. Most commonly, the desired result is to drive consumer behavior with respect to a commercialoffering, although political and ideological advertising is also common. This type of work belongs to a categorycalled affective labor. General public is exposed to advertisements in media such as newspapers, television,outdoor, cinema and cyber media. The advertisers, i.e., the manufacturers of products and the providers ofservices try to communicate the superiority and advantages of their products or services through theadvertisements. In a highly competitive market scenario, the advertisers have to compete for the attention of thepublic.